Neutrophil-mediated carbamylation promotes articular damage in rheumatoid arthritis - O’Neil, Liam J.; Barrera-Vargas, Ana; Sandoval-Heglund, Donavon; Merayo-Chalico, Javier; Aguirre-Aguilar, Eduardo; Aponte, Angel M.; Ruiz-Perdomo, Yanira; Gucek, Marjan; El-Gabalawy, Hani; Fox, David A.; Katz, James D.; Kaplan, Mariana J.; et al. (Science advances, 2020)
Carbamylated histone antibodies potentiate osteoclast formation and associate with bone erosion in rheumatoid arthritis. Formation of autoantibodies to carbamylated proteins (anti-CarP) is considered detrimental in the prognosis of erosive rheumatoid arthritis (RA). The source of carbamylated antigens and the mechanisms by which anti-CarP antibodies promote bone erosion in RA remain unknown. Here, we find that neutrophil extracellular traps (NETs) externalize carbamylated proteins and that RA subjects develop autoantibodies against carbamylated NET (cNET) antigens that, in turn, correlate with levels of anti-CarP. Transgenic mice expressing the human RA shared epitope (HLADRB1* 04:01) immunized with cNETs develop antibodies to citrullinated and carbamylated proteins. Furthermore, anti–carbamylated histone antibodies correlate with radiographic bone erosion in RA subjects. Moreover, anti–carbamylated histone–immunoglobulin G immune complexes promote osteoclast differentiation and potentiate osteoclast-mediated matrix resorption. These results demonstrate that carbamylated proteins present in NETs enhance pathogenic immune responses and bone destruction, which may explain the association between anti-CarP and erosive arthritis in RA.